Consorced organic fertilizer with grasses for growing mushroom ganoderma lucidum - Saad, André Luiz Merthan [UNESP]; Lima, Fernanda Silva; De Andrade, Meire Cristina Nogueira [UNESP] (Centro Universitario de Maringa, 2018)
The use of organic fertilizer with two types of grass, coast-cross (Cynodon dactylon (L.) Pers) and lucerne/alfafa grass (Medicago sativa L.), was analyzed and compared to traditional substrate enriched with wheat bran. Two strains of Ganoderma lucidum, 144 and 351, were used to identify the best option for the substrate. Evaluation criteria comprised the chemical composition of the substrates, biological efficiency and the amount of fresh basidioms and the number of basidioms. Four substrates were tested, namely, S-1 (alfafa + bran), S-2 (alfafa + organic fertilizer), S-3 (coast-cross + bran), S-4 (coast-cross + organic fertilizer), with the two G. lucidum strains. Experiment comprised ten replications, with 80 packages with 700 g of substrate each. Treatments also received 80% grass, 18% wheat bran or organic fertilizer and 2% limestone, with 60% humidity. Best means for EB, MBF and NB showed that S2 (alfafa + fertilizer) and S4 (coast-cross + fertilizer) were the substrates with the best agronomic results. Strain 144 of G. lucidum had the best result and yield in productivity.
ADUBO ORGÂNICO CONSORCIADO COM GRAMÍNEAS PARA O CULTIVO DO COGUMELO Ganoderma lucidum
Keywords: Grass; Mushrooms; Substrates